A computational framework for post‐TAVR cardiac conduction abnormality (CCA) risk assessment in patient‐specific anatomy. Issue 7 (7th February 2022) - Reza, Symon; Bianchi, Matteo; Kovarovic, Brandon; Anam, Salwa; Slepian, Marvin J.; Hamdan, Ashraf; Haj‐Ali, Rami; Bluestein, Danny
Abstract: Background: Cardiac conduction abnormality (CCA)‐ one of the major persistent complications associated with transcatheter aortic valve replacement (TAVR) may lead to permanent pacemaker implantation. Localized stresses exerted by the device frame on the membranous septum (MS) which lies between the aortic annulus and the bundle of His, may disturb the cardiac conduction and cause the resultant CCA. We hypothesize that the area‐weighted average maximum principal logarithmic strain (AMPLS) in the MS region can predict the risk of CCA following TAVR. Methods: Rigorous finite element‐based analysis was conducted in two patients (Balloon expandable TAVR recipients) to assess post‐TAVR CCA risk. Following the procedure one of the patients required permanent pacemaker (PPM) implantation while the other did not (control case). Patient‐specific aortic root was modeled, MS was identified from the CT image, and the TAVR deployment was simulated. Mechanical factors in the MS region such as logarithmic strain, contact force, contact pressure, contact pressure index (CPI) and their time history during the TAVR deployment; and anatomical factors such as MS length, implantation depth, were analyzed. Results: Maximum AMPLS (0.47 and 0.37, respectively), contact force (0.92 N and 0.72 N, respectively), and CPI (3.99 and 2.86, respectively) in the MS region were significantly elevated in the PPM patient as compared to control patient. Conclusion: Elevated stresses generated by TAVR devices during deployment appear to correlate with CCA risk, with AMPLS in the MS region emerging as a strong predictor that could be used for preprocedural planning in order to minimize CCA risk. Abstract : This study employs rigorous computational techniques to assess the risk of post‐TAVR cardiac conduction abnormality in patient‐specific anatomy. Among various factors analyzed in this study, area‐weighted average of the maximum principal logarithmic strain exerted by the TAVR prosthesis in the membranous septum region during the device deployment was found to be a strong predictor for assessing CCA risk associated with TAVR devices. Such patient specific studies could further be used for preprocedural planning in order to minimize the CCA risk.